Statisics: an introduction using R - Crawley, Michael J. (New Delhi: Wiley India Publication, 2014)
Statistics: An Introduction Using R This book offers extensive coverage of many basic and more advanced statistical methods, concentrating on graphical inspection, and features step-by-step instructions to help the non-statistician to understand fully the methodology. The computing is done in S-Plus, which is globally recognized as one of the most powerful and flexible statistical software packages and is available via a freeware Programme called R. No existing book covers such a broad array of statistical methods, at a level which is elementary enough to appeal to such a broad range of disciplines. Contents Preface Fundamentals Dataframes Central Tendency Variance Single Samples Two Samples Statistical Modelling.
Fundamentals -- Dataframes -- Central Tendency -- Variance -- Single Samples -- Two Samples -- Statistical Modelling -- Regression -- Analysis of Variance -- Analysis of Covariance -- Multiple Regressions -- Contrasts -- Count Data -- Proportion Data -- Death and Failure Data -- Binary Response Variable -- Fundamentals of the R Language
Includes index and references.
Keywords: Statistics; Statistical theory and methods; Fundamental Statistics; Mathematical Statistics